Headgroup engineering in mechanosensitive membrane probes. Issue 100 (30th November 2016) - Soleimanpour, Saeideh; Colom, Adai; Derivery, Emmanuel; Gonzalez-Gaitan, Marcos; Roux, Aurelien; Sakai, Naomi; Matile, Stefan
Abstract : Tricky chemistry had to be addressed to make mechanosensitive membrane probes ready for use, including a chalcogen-bond mediated "molecular guillotinylation". Abstract : Systematic headgroup engineering yields planarizable push–pull flipper probes that are ready for use in biology – stable, accessible, modifiable –, and affords non-trivial insights into chalcogen-bond mediated mechanophore degradation and fluorescence enhancement.